1979
DOI: 10.1111/j.1432-1033.1979.tb12997.x
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Size and Shape of the Folch‐Pi Apoprotein in Aqueous and Organic Solvents

Abstract: In 1 % acetic acid, sedimentation velocity measurements and equilibrium ultracentrifuge experiments demonstrate that the Folch-Pi apoprotein is not monodisperse. The weight-average molecular weight calculated from ultracentrifuge experiments and combining sedimentation coefficient and viscosity measurements, ranged from 64000 to 80000. The intrinsic viscosity value suggests an asymetric shape for the apoprotein if a low value of hydration is considered.In dioxan/lx acetic acid (2: 3, v/v) a smaller sedimentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In the present work we demonstrated that under some specific experimental conditions (low water content) 100% of the aqueous form of PLA was incorporated in lipid bilayers. This indicates-in agreement with previous data (Lavialle et al, 1979)-that the Folch-Pi apoprotein exhibits a conformational adaptability to its surrounding solvent medium. Therefore, it could be suggested that in the cell this protein could migrate from the endoplasmic reticulum lumen to the plasmic membrane under the so-called aqueous form.…”
Section: Discussionsupporting
confidence: 93%
“…In the present work we demonstrated that under some specific experimental conditions (low water content) 100% of the aqueous form of PLA was incorporated in lipid bilayers. This indicates-in agreement with previous data (Lavialle et al, 1979)-that the Folch-Pi apoprotein exhibits a conformational adaptability to its surrounding solvent medium. Therefore, it could be suggested that in the cell this protein could migrate from the endoplasmic reticulum lumen to the plasmic membrane under the so-called aqueous form.…”
Section: Discussionsupporting
confidence: 93%
“…These higher values can be reconciled with our measured number of first shell lipids if it is assumed that the protein is oligomeric in the membrane, hence reducing the number of available surface sites per monomer. Light-scattering experiments have indicated that the protein is not monomeric in 2-chloroethanol, from which the lipid-protein complexes were formed (Lavialle et al, 1979). Sedimentation-equilibrium experiments have also indicated that the protein is a hexamer in nondenaturing detergents (Smith et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Although the myelin proteolipid apoprotein may be obtained in soluble form from either organic solvents or aqueous solutions, the structural studies described above were performed by adding the appropriate lipids to the organic solution of the apoprotein. Since significant conformational and molecular weight differences arise for the apoprotein depending upon the solvent system used in its prepa-ration (Sherman & Folch-Pi, 1970;Nicot et al, 1973;Lees et al, 1979; Nguyen Le et al, 1976;Lavialle et al, 1979), we examine the vibrational data for the reconstituted bilayer systems which specifically incorporated the apoprotein prepared in aqueous medium. These spectral data indicate that this form of the apoprotein induces substantially different bilayer effects depending upon the degree of unsaturation within the hydrophobic region of the lipid matrix.…”
mentioning
confidence: 99%